2008
DOI: 10.1159/000159266
|View full text |Cite
|
Sign up to set email alerts
|

A Treatment Selection Protocol for Recurrent Ovarian Cancer Patients: The Role of FDG-PET/CT and Staging Laparoscopy

Abstract: Objective: To investigate the best diagnostic and staging strategy for recurrent ovarian cancer. Methods: The negative predictive value, specificity, positive predictive value, sensitivity, and accuracy rates of the fluorine-18-fluorodeoxyglucose positive emission tomography computed tomography (FDG-PET/CT) and staging laparoscopy in identifying surgically treatable/untreatable patients are assessed in a consecutive series of 70 recurrent ovarian cancer cases. Moreover, the diagnostic performance of each stagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(31 citation statements)
references
References 68 publications
0
31
0
Order By: Relevance
“…All Cases were submitted to complete blood work (blood count, tests blood chemistry, urine analysis and Ca125 serum levels), FDG-PET/CT scan and staging-laparoscopy (S-LPS) to exclude extra-abdominal disease and to assess the chances of optimal cytoreduction [12].…”
Section: Treatmentmentioning
confidence: 99%
“…All Cases were submitted to complete blood work (blood count, tests blood chemistry, urine analysis and Ca125 serum levels), FDG-PET/CT scan and staging-laparoscopy (S-LPS) to exclude extra-abdominal disease and to assess the chances of optimal cytoreduction [12].…”
Section: Treatmentmentioning
confidence: 99%
“…Staging laparoscopy has proved to offer a reliable evaluation of occult peritoneal carcinosis, and a good prediction of the possibility of optimal cytoreduction in primary and recurrent ETOC patients [24,25,26]. Conversely, retroperitoneal and intraparenchymal localizations of disease may be missed by laparoscopic exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Such techniques should be considered complementary because of the potential of each one to identify a different setting of the disease [25]. …”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that an objective evaluation of the complete debulking is available for primary advanced cases utilizing a laparoscopic predictive index score (40)(41). In addition, the inclusion of S-LPS can reduce the risk of explorative laparotomies to about 10%, with respect to 20% and 30% obtained with the classical criteria of evaluation of response.…”
Section: Laparoscopic Assesment Of Disease Extent and Potential For Rmentioning
confidence: 99%
“…The explanation to this, could be the presence of radiological artifacts due to the effects of chemotherapy, such as adherences or fibrosis secondary to tumor shrinkage, which would probably alter the diagnostic performances of conventional images. The laparoscopic predictive score of surgical outcome www.intechopen.com has been shown to be reliable in selected group of patients (41)(42). The laparoscopic parameters meeting the inclusion criteria have been mesenteral retraction, bowel and stomach infiltration, and superficial liver metastases.…”
Section: Laparoscopic Assesment Of Disease Extent and Potential For Rmentioning
confidence: 99%